Tratamento de águas residuárias da indústria têxtil por biossorção - Silva, Daniela da (2017)
The high consumption of water by the industries and their subsequent disposal, are environmental concerns due to the problem of water scarcity and contamination of the water bodies. The textile industries are responsible for a large part of the water use, since their industrial processes demand large quantities, since it spends at least 150 liters of water in the production of a woof. The steps of dyeing, softening and washing release large quantities of dyes and these, in turn, when into contact with the water body, dificult the penetration of light, thus damaging the biological processes that occur there. The textile effluent, object of study of this work, comes from a textile industry located in Francisco Beltrão. The state of Paraná is a major producer of pinion bark, and in this way the bark was, used as a biosorbent for the removal of dyes from textile effluents. A chemical treatment was carried out in the shell with sulfuric acid in order to improve the surface area and through analyzes like zero load point and Boehm titration, it was possible to identify that the surface of the shell is predominantly acidic. The bark underwent to a proximate analysis in order to identify the percentages of ash, fixed carbon, total solids and volatile material and the values found were similar to those of other works with the pinion bark. The effluent also underwent characterization analyzes, among them, the series of solids that identified the presence of dissolved salts from the production stage of the company. The COD found for the raw effluent is outside of the standards required by the legislation, but, this analysis was performed on the effluent before undergoing any treatments and the found value of 3016,67 mgO2/L is in agreement with the COD value of textile effluents. Dilutions of the raw effluent were carried out in order to obtain a calibration curve with the concentration for this effluent. From the experimental planning some parameters that interfere in the adsorption, such parameters are pH = 3 and room temperature. The adsorption kinetics were performed under these conditions, in a bench batch reactor that remained in agitation at 150 rpm's for 24 hours and after this period, the experimental data as adjusted to kinetic models of pseudo 1st and 2nd order. The best fit was the pseudo 2nd orders with R² = 0.9893 and qmax = 8.928 mg/g which obtained a greater approximation to the experimental q. The color removal was around 42% in 24 hours under agitation. Because it is a real effluent and with many unknown compounds, it is considered a considerable percentage of removal. However, when conducting the analyzes to verify if the effluent is suitable for the reuse, it can not be applied, since after passing through the adsorption process, the parameters required by the legislation were in disagreement with the values found. New treatment approaches are suggested for the pinion bark in order to obtain a biosorbent with greater adsorption capacity.